2022
DOI: 10.1002/jev2.12261
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis is associated with Rab27‐independent expulsion of extracellular vesicles containing RIPK3 and MLKL

Abstract: Extracellular vesicle (EV) secretion is an important mechanism used by cells to release biomolecules. A common necroptosis effector—mixed lineage kinase domain like (MLKL)—was recently found to participate in the biogenesis of small and large EVs independent of its function in necroptosis. The objective of the current study is to gain mechanistic insights into EV biogenesis during necroptosis. Assessing EV number by nanoparticle tracking analysis revealed an increased number of EVs released during necroptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 61 publications
(85 reference statements)
2
22
1
Order By: Relevance
“…In the present work, cdEVs released following different RCD modalities exhibit strong similarities in biophysical properties and protein composition, suggesting the involvement of a common pathway in their biogenesis and cargo loading. Here, we reported the presence of tetraspanin (CD63, CD81), lipid raft-associated proteins flotillin-1 and -2, and ESCRT-III components (CHMP2-A and -B), in agreement with previous reports on apoptotic (Park et al, 2018;Tucher et al, 2018), necroptotic (Gupta et al, 2022;Shlomovitz et al, 2021;Yoon et al, 2017;Zargarian et al, 2017) and ferroptotic EVs (Brown et al, 2019;Ito et al, 2021;Kajiwara et al, 2022). However, the amount of these classically used exosomal markers (CD63, CD81, CHMP2A, CHMP2B, CHMP4B, CHMP4C, TSG101, FLOT1, FLOT2, Alix, nSMase) was quite similar between the different cdEVs, and they were relatively underrepresented in cdEVs compared to ssEVs, as revealed by proteomics.…”
Section:  Discussionsupporting
confidence: 93%
“…In the present work, cdEVs released following different RCD modalities exhibit strong similarities in biophysical properties and protein composition, suggesting the involvement of a common pathway in their biogenesis and cargo loading. Here, we reported the presence of tetraspanin (CD63, CD81), lipid raft-associated proteins flotillin-1 and -2, and ESCRT-III components (CHMP2-A and -B), in agreement with previous reports on apoptotic (Park et al, 2018;Tucher et al, 2018), necroptotic (Gupta et al, 2022;Shlomovitz et al, 2021;Yoon et al, 2017;Zargarian et al, 2017) and ferroptotic EVs (Brown et al, 2019;Ito et al, 2021;Kajiwara et al, 2022). However, the amount of these classically used exosomal markers (CD63, CD81, CHMP2A, CHMP2B, CHMP4B, CHMP4C, TSG101, FLOT1, FLOT2, Alix, nSMase) was quite similar between the different cdEVs, and they were relatively underrepresented in cdEVs compared to ssEVs, as revealed by proteomics.…”
Section:  Discussionsupporting
confidence: 93%
“…Unlike "apoptotic bodies, " "necroptotic bodies" do not appear to contain DNA. These necroptotic bodies can probably modulate the inflammatory response of surrounding cells (Edry-Botzer and Gerlic, 2017;Gupta et al, 2022). It remains to be investigated whether "necroptotic bodies" can undergo phagocytosis.…”
Section: Mechanism Of Necroptosismentioning
confidence: 99%
“…It is a regulated form of necrotic cell death mediated by receptor-interacting kinase 1 (RIPK1), receptor-interacting protein kinase 3 (RIPK3), and mixed lineage kinase domain-like (MLKL) ( Conrad et al, 2016 ; Cao et al, 2022 ). RIPK1 activates RIPK3 and thereby recruits MLKL at the cell membrane, which causes membrane rupture and eventually triggers necroptosis ( Samson et al, 2021 ; Gupta et al, 2022 ). Necroptosis is involved in cell death associated with ICH ( Galluzzi et al, 2018 ).…”
Section: The Crosstalk Between Ferroptosis and Other Traditional Cell...mentioning
confidence: 99%
“…Neurovascular injury and related hemolysis of extravasated erythrocytes post-ICH producing hemoglobin degradation metabolites may trigger the neuroinflammatory response of surrounding astroglia resulting in activation of the necroptotic pathway. Meanwhile, Necrostatin-1, a specific RIPK1 inhibitor, has been shown to reduce cell death, hematoma volume, and neurobehavioral outcomes in a mouse model of ICH ( Gupta et al, 2022 ). Numerous reports have suggested that ferroptosis is always accompanied by necroptosis ( Lv et al, 2021 ).…”
Section: The Crosstalk Between Ferroptosis and Other Traditional Cell...mentioning
confidence: 99%